XCMS-METLIN: data-driven metabolite, lipid, and chemical analysis - Martin Giera; Aries Aisporna; Winnie Uritboonthai; Linh Hoang; Rico J E Derks; Kara M Joseph; Erin S Baker; Gary Siuzdak (Molecular Systems Biology)
In this Correspondence, G. Siuzdak and colleagues present XCMS-METLIN, an extensive resource for metabolomics, lipidomics, and chemical analysis.